HEART DISEASE PREDICTION USING BIO INSPIRED ALGORITHMS (International Journal of Food and Nutritional Sciences, 2022)
Health diseases are increasing day by day due to life style and hereditary. In this aspect,heart disease is the most important cause of demise in the human kind over past fewyears. The objective of this paper is to predict the Heart Disease by applying ArtificialNeural Network using swarm Intelligence algorithm. Swarm intelligence (SI) is relativelynew interdisciplinary field of research. The Swarm-based algorithms have recentlyemerged as a family of nature-inspired, population-based algorithms that are capable ofproducing low cost, fast, and robust solutions to several complex problems.